Day 2 Tue, April 26, 2022 2022
DOI: 10.2118/209452-ms
|View full text |Cite
|
Sign up to set email alerts
|

Revised Correlation for Accurate Estimation of CO2-Brine Interfacial Tension at Reservoir Conditions

Abstract: A recently reported correlation of CO2–brine interfacial tension (IFT) for the full range of reservoir pressure, temperature, and formation water salinity necessary to evaluate CO2 sequestration in hydrocarbon reservoirs has been revised and simplified. The new CO2–brine correlation predicts CO2–brine IFT normalized by water surface tension from temperature, CO2-water density difference normalized by the density difference between water and it's vapor(function of pressure and temperature), and the valence-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…However, the SAFT EoS is too complicated and requires too many factors and parameters. Most recently, Jerauld et al [58] proposed a revised correlation method for the accurate estimation of the CO 2 -brine IFT based on over 1600 data points from the literature and concluded that the Kashefi [59] method has better qualitative behavior and improves predictions with an AARE of approximately 5%. Neural network-and machine learning-based models have high computing speeds, strong adaptability, and a fault-tolerant ability; however, the normalization method lacks thermodynamic meaning.…”
Section: Interfacial Tension Between Co 2 and Water/brinementioning
confidence: 99%
“…However, the SAFT EoS is too complicated and requires too many factors and parameters. Most recently, Jerauld et al [58] proposed a revised correlation method for the accurate estimation of the CO 2 -brine IFT based on over 1600 data points from the literature and concluded that the Kashefi [59] method has better qualitative behavior and improves predictions with an AARE of approximately 5%. Neural network-and machine learning-based models have high computing speeds, strong adaptability, and a fault-tolerant ability; however, the normalization method lacks thermodynamic meaning.…”
Section: Interfacial Tension Between Co 2 and Water/brinementioning
confidence: 99%